The influence of leadership, values, and motivation on organizational culture in MSME actors - Kurniyati, Nany Noor; Surya, Huda (PHINISI, 2025)
This study aims to analyze the influence of leadership, organizational values, and motivation on organizational culture within the Sri Tanjung MSME Association in Yogyakarta City. The main focus is to examine how these three factors contribute to shaping a solid organizational culture among MSME actors. A quantitative descriptive research design was employed. The population consisted of 90 members of the Sri Tanjung Association, with a saturated sampling technique. Data were collected using a questionnaire based on a five-point Likert scale. The data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.2.8. Validity was tested through convergent and discriminant validity, while reliability was measured using composite reliability and Cronbach’s Alpha. The findings indicate that organizational values exert the strongest influence on organizational culture, with a coefficient of 1.249 (p < 0.05). Motivation also shows a significant effect (p = 0.005), although the direction is negative (-0.962), suggesting the need for further investigation into the dominant type of motivation. Meanwhile, leadership does not significantly affect organizational culture (p = 0.260). Overall, the research model explains 66.5% of the variance in organizational culture (R² = 0.665). In conclusion, organizational values are the dominant factor shaping MSME organizational culture, followed by motivation and leadership. Strengthening organizational culture should prioritize the internalization of shared values, the adjustment of leadership styles to the organizational context, and the management of motivation to support collective values. Through this approach, the Sri Tanjung MSME Association can foster a more solid, adaptive, and sustainable organizational culture.